Colorectal cancer: awareness of the symptom / Nurul Fatin Farhana Mohd Zaini - Mohd Zaini, Nurul Fatin Farhana (Faculty of Art and Design, 2020)
This project is to create awareness about the cancer among Malaysian where people are not aware about the symptoms.